Retinopathy and Neuropathy in Patients with End Stage Renal Disease on Haemodialysis- A Hospital Based Study (Anwer Khan Modern Medical College Journal, 2015)
Bacground: Chronic renal failure is irreversible and progressive process that results in end stage renal disease (ESRD) where the patient has to be dependent on renal replacement therapy for survival. Retinopathy and neuropathy are often asymptomatic in their most treatable stage; delay in diagnosis can result in significant increase in the patient's risk of visual loss and disability. Ocular condition is also an indicator of the metabolic control of the disease process. This study is an attempt to access the ocular status/complications as well as neurological manifestation associated with end stage renal disease on haemodialysis.Methodology: This is a cross sectional descriptive type of observational study on patients of end stage renal disease getting haemodialysis in Medical College for Women and Hospital. Duration of study was 3 years from January 2011 to December 2013. This study is an attempt to access the ocular status/complications as well as neurological manifestation associated with end stage renal disease on haemodialysis.Result: Among 81 patients, 42 patients had hypertension (HTN) and 19 had diabetes mellitus (DM) and 20 had other causes of chronic kidney disease(CKD). In our study, out of 19 patients of diabetes mellitus, 73.68%(14) had diabetic retinopathy(DR) and 26.32%(5) had normal fundus. All the 42 patients had hypertensive retinopathy(HR). Regarding fundal examination of patients with hypertensive retinopathy(HR), 32.26% had gradel, and 17.74%, 43.55% and 6.45% were of grade ll, lll, lV respectively. It was found that non-proliferative changes in ocular fundal examination in diabetic patients were the commonest abnormality. On fundal examination of diabetic retinopathy (DR), 26.32% had normal fundus, 26.32% had dot and blot haemorrhages, 21.05% had hard exudates and cotton wool, 21.05% had new vascularization while 5.26% had retinal detachment.The following types of neuropathy were seen among our patients; 48.15% had symmetrical distal sensory motor polyneuropathy, 19.75% had a symmetrical polyneuropathy, 19.75% had mononeuropathy and cranial nerve palsies were detected in 12.35%.Conclusion: Detailed ocular and neurological examination should be undertaken in patients of end stage renal disease(ESRD) on maintenance haemodialysis(HD) for early diagnosis and treatment of the complications. Awareness is needed of the potential ocular and neurological complications of the disease process.Anwer Khan Modern Medical College Journal Vol. 6, No. 1: January 2015, Pages 14-19